2019
DOI: 10.1016/j.jebo.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Group formation and cooperation in social dilemmas: A survey and meta-analytic evidence

Abstract: We survey the growing literature on group formation in the context of three types of social dilemma games: public goods games, common pool resources, and the prisoner's dilemma. The 62 surveyed papers study the effect of different sorting mechanisms-endogenous, endogenous with the option to play the game, and exogenous-on cooperation rates. Our survey shows that cooperators are highly sensitive to the presence of free-riders, independently of the sorting mechanism. We complement the survey with a meta-analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…These findings complement the literature studying the effects of group mergers on performance and norm transmission in groups (Charness and Yang [28]; Ehrhart and Keser [29]; Gürerk et al [30]; Guido et al [31]; Feiler and Camerer [32]; Ranehill et al [33]; Weber and Camerer [34]; Weber [35]). 2 Feiler and Camerer [32] for example, study endogenous group mergers in an experiment (i.e., group mergers in which group members decide whether or not and with whom to merge).…”
Section: Introductionsupporting
confidence: 81%
“…These findings complement the literature studying the effects of group mergers on performance and norm transmission in groups (Charness and Yang [28]; Ehrhart and Keser [29]; Gürerk et al [30]; Guido et al [31]; Feiler and Camerer [32]; Ranehill et al [33]; Weber and Camerer [34]; Weber [35]). 2 Feiler and Camerer [32] for example, study endogenous group mergers in an experiment (i.e., group mergers in which group members decide whether or not and with whom to merge).…”
Section: Introductionsupporting
confidence: 81%
“…At a broader group level, similarity promotes group cohesion (Turner et al, 1992 ), and information about the similarities between ingroups and outgroups results in more positive attitudes toward the outgroups (Hanel et al, 2019 ). Similarly, the success of a sorting method in matching like-minded individuals has proven to be interlinked with cooperation (Guido et al, 2019 ). Burlando and Guala ( 2005 ) categorized participants according to their investment in social dilemmas as cooperators, reciprocators, free riders, and noisy, and grouped same-categorized participants to complete repeated public goods tasks.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…However, the difference between the C, C, C and C, S, S groups was pronounced, and the cooperation level of the S, S, S group was significantly lower than that of the other groups. In other words, a match of cooperative individuals can maintain both group-level and individual-level cooperation at a high level (Guido et al, 2019 ). However, classifications in these studies are based on participants’ behavioral patterns rather than inherent traits and values, which raises the question of whether the coherence of inherent qualities, including SVO similarity, can affect cooperation.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many empirical studies have shown that group norms facilitate cooperation [14,30,31], and cooperative norms have also been proven to be a mediator of the CC effect [23]. While most researchers agree with these findings, they have differing opinions regarding the most suitable theory for explaining how CCs influence cooperation via perceived group norms.…”
Section: Effect and Moral Elevationmentioning
confidence: 99%